Substitution of Flour Sea Grapes (Caulerpa racemosa) Fermented On Tilapia (Oreochromis niloticus) Feed - Amelia, Deby Ariska; Lumbessy, Salnida Yuniarti; Lestari, Dewi Putri (JURNAL AKUAKULTURA, 2025)
One way to minimize the fiber content and maximize the other nutritional content in seaweed can be done through the fermentation process. This research aims to analyze the effect of substitution of fermented sea grape (Caulerpa racemosa) flour in tilapia (Oreochromis niloticus) feed formulations. The research was carried out at the Fish Production and Reproduction Laboratory, Mataram University for 50 days from March - May 2022. The research used an experimental method with a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications, namely control (P1), fermented sea grape flour 4% dose (P2), fermented sea grape flour 8% dose (P3), and fermented sea grape flour 12% dose (P4). Data were analyzed using Analysis of Variance (ANOVA) and continued with Duncan's advanced test. The research results showed that the average absolute weight of tilapia ranged from 9.43-11.58 g/fish, absolute length ranged from 2.24-2.90 cm/fish, Specific Growth Rate (LPS) ranged from 2.36-2, 64%/day, Feed Utilization Efficiency (EPP) ranges from 76.8-95.8%, Feed Conversion Ratio (FCR) ranges from 1.05-1.31 and Survival Rate (SR) ranges from 90-97%. The addition of fermented C. racemosa sea grape flour concentration can affect the absolute weight of tilapia, but does not affect absolute length, specific growth rate, FCR, EPP and SR values. The addition of C. racemosa sea grape flour fermented with Lactobacillus casei and Saccharomyces cerevisiae to a concentration of 4% (P2) gave the best results because it could increase the absolute weight of tilapia by 11.58 g/fis.sea grapes